VISUALISASI RUMAH IDAMAN DENGAN PERANGKAT KOMPUTER KENDALI INTERAKSI ALAMI - Muhaimin, Muhammad Yahya; H., Humaidi; Affan, Ibnu (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
We realize that a dream house is one of the most important objectives for many families. To do this they even do not hesitate to hire a house consultant with high payment. Virtual reality technology actually could answer this problem. People can design their house with the easiest and cheapest way. By exploring, designing, configuring, testing and demonstrating computer hardware and software, we have successfully created a representative tool on house design. All-in-One PC, Kinect and TurboFLOORPLAN are the tool set to make a natural interaction between user and computer to reach an enjoyable home design system.